2018
DOI: 10.1080/10253890.2018.1429398
|View full text |Cite
|
Sign up to set email alerts
|

Investigating relations among stress, sleep and nail cortisol and DHEA

Abstract: In the current study, we present data investigating the relationships among stress, sleep disturbance, self-control, and levels of cortisol (CORT) and dehydroepiandrosterone (DHEA) in fingernail clippings. Currently, hair CORT is the only routinely used noninvasive, validated, biomarker of chronic exposure to stress-related hormones. Nail clippings represent an important potential alternative sample matrix for assessing chronic hormone exposure, as it offers a different timeline of hormone incorporation than s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Among infants, nail DHEA was positively associated with prenatal stress in the first trimester, with nail DHEA positively associated with infant irritability (Mikoteit et al, ). Nail DHEA in the previously mentioned study on low‐income minority adolescents was also shown to be positively associated with stressful events, sleep disturbance, and waking (Doan et al, ). In another study with 33 university students, an increase in the ratio between nail cortisol and nail DHEA was observed during a stressful period in the semester.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Among infants, nail DHEA was positively associated with prenatal stress in the first trimester, with nail DHEA positively associated with infant irritability (Mikoteit et al, ). Nail DHEA in the previously mentioned study on low‐income minority adolescents was also shown to be positively associated with stressful events, sleep disturbance, and waking (Doan et al, ). In another study with 33 university students, an increase in the ratio between nail cortisol and nail DHEA was observed during a stressful period in the semester.…”
Section: Introductionmentioning
confidence: 80%
“…As noted, there has been very little characterization of the contexts among studies using hair or nail cortisol, with studies mostly relying on simple measures of socioeconomic status. For instance, only a few hair cortisol studies have made minority and low‐income children and families a focus of study (Doan et al, ; Liu et al, ; Rippe et al, ; Vaghri et al, ). Given the very little variation in context among most studies, there remains a limited understanding regarding the influence of context on hair and nail cortisol across development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Allostatic load is an inability of the body's systems to accommodate adequately stress challenge due to chronic stressThis accompanies the modern lifestyle and impairs normal levels of stress mediators including cortisol (CORT). 4 Therefore elevated CORT levels reflect decreased body's ability to counteract consequences of chronic stress, 5,6 and to support quality of life. 7 Accordingly, fluctuating blood levels of CORT have been correlated with certain individual's behaviors such as heavy cigarettes smoking, 8 heavy coffee consumption, 9 sleep deprivation, 10 overweight, 11,12 and hyperlipidemaia.…”
Section: Introductionmentioning
confidence: 99%